Age of first arrest varies by gambling status in a cohort of young adults. (15th March 2014) - Martins, Silvia S.; Lee, Grace P.; Santaella, Julian; Liu, Weiwei; Ialongo, Nicholas S.; Storr, Carla L.
<x xml:space="preserve">Abstract</x> Background and Objectives To describe the association between social and problem gambling and first criminal arrest by age 23 in a cohort of urban, mainly African‐American youth. Methods Data for this study were derived from several annual interviews being completed on a community sample of 617 participants during late adolescence until age 23. Information on gambling status, engagement in deviant behaviors, illegal drug use, and arrest history were collected through yearly interviews. Analysis was carried out using Nelson–Aalen cumulative hazard models and simple and adjusted Cox proportional hazards models. Results More problem gamblers had been arrested before age 23 than social gamblers and non‐gamblers, ie, 65% of problem gamblers were arrested before age 23, compared to 38% of social gamblers and 24% non‐gamblers. Social gambling was only significantly associated with the hazard of first arrest by age 23 in the unadjusted model (HR: 1.6, p < .001), but not after adjustment for covariates (HR: 1.1, p = .47). Problem gambling was significantly associated with the hazard of first arrest by age 23 years in the unadjusted (HR: 3.6, p < .001) and adjusted models (HR: 1.6, p = .05). Conclusions and Scientific Significance Problem gambling was significantly associated with earlier age of being arrested. Dilution effects after adjustment for several deviant behaviors and illegal drug use by age 17 suggest that youth exposure to certain common factors may result in engagement in multiple risky behaviors, including problem gambling. Studies are needed to investigate the developmental pathways that lead to these combined behaviors among youth. (Am J Addict 2014;23:386–392)